Nutritional status and physical performance of urban high school students from two income groups - Callanta, Luz Socrates
A study to determine the relationship between nutritional status and physical performance of adolescents, was conducted involving 141 low-income and 109 middle-income high school students. Results showed that nutrient intakes of middle-income adolescents were generally higher than those of low-income adolescents. Middle-income subjects were also taller and heavier. Both income groups had acceptable levels of hemoglobin. Physical performance scores showed all tests favoring the middle-income group, both male and female, except for muscular endurance which favored the low-income females. Correlation analyses showed that scores for muscular strength, speed, agility, power and abdominal strength endurance increased with increased calorie and carbohydrate intake and higher dietary iron adequacy. Speed also increased with increased fat intake and adequacy of calorie intake. Muscular strength improved with protein intake. Abdominal strength endurance, power and muscular strength likewise increased with an increase in height, weight, and hemoglobin levels. With increased hemoglobin levels, improvement in speed and agility was observed. The same relationship was observed between height and cardiovascular endurance as well as between weight and speed. Muscular endurance band flexibility were not significantly related to nutrient intake, height, weight or hemoglobin levels. Cardiovascular endurance was not also affected by any nutrient intake.